(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study explores the key facets of the Satavahana dynasty’s governance and economic system. The Satavahana Dynasty, ruling from approximately the 2nd century BCE to the 3rd century CE, was a prominent power in ancient India, renowned for its influential political and economic structures. Politically, the Satavahanas established a centralized monarchy characterized by the king’s supreme authority over both administration and military affairs. The administrative framework was organized into provinces, each governed by officials appointed by the king. This central authority was complemented by a feudal system, where local rulers or feudatories were granted autonomy in return for loyalty and military support. The dynasty’s military organization was well-structured, including infantry, cavalry, and war elephants, which played a crucial role in territorial expansion and defense. Succession to the throne was primarily hereditary, though it was often challenged by internal conflicts and rival claims. Economically, the Satavahanas thrived on agriculture, benefiting from the fertile river valleys in their territories. Agriculture supported not only local sustenance but also trade. The dynasty controlled key trade routes linking the Indian interior with the western coast, fostering extensive commerce with regions as far-reaching as the Roman Empire. The issuance of standardized coinage facilitated economic transactions and trade, further integrating the economy. Urbanization and infrastructure development in major cities like Amaravati and Ujjain bolstered economic activities and cultural exchanges. The Satavahana Dynasty’s political and economic systems, combined with their patronage of Buddhism and urban growth, significantly shaped ancient India’s historical trajectory, leaving a lasting impact on the region’s political, economic, and cultural landscape.